eNOS T-786C polymorphism affects atorvastatin-induced changes in erythrocyte membrane fluidity - Nagassaki, S.; Herculano, R. D.; Graeff, Carlos Frederico de Oliveira [UNESP]; Tanus-Santos, J. E. (Springer, 2009)
Statins have pleiotropic effects, including endothelial nitric oxide synthase (eNOS) upregulation and increased nitric oxide formation, which can be modulated by a genetic polymorphism in the promoter region of the eNOS gene (T-786C). Here, we report our investigation of whether this polymorphism modulates the effects of atorvastatin on the fluidity of erythrocyte membranes.We genotyped 200 healthy subjects (males, 18-60 years of age) and then randomly selected 15 of these with the TT genotype and 15 with the CC genotype to receive placebo or atorvastatin (10 mg/day oral administration) for 14 days. Cell membrane fluidity was evaluated by electron paramagnetic resonance (EPR) and spin-labeling method. The EPR spectra were registered on a VARIAN-E4 spectrometer. Thiobarbituric acid-reactive species (TBA-RS) and plasma membrane cholesterol were determined in the erythrocytes.Atorvastatin reduced membrane fluidity in CC subjects (P < 0.05) but not in those with the TT genotype (P > 0.05). While no significant differences were found in plasma membrane cholesterol concentrations, higher TBA-RS concentrations were found in the CC subjects than in the TT subjects (P < 0.05).These findings suggest that a short treatment with atorvastatin is disadvantageous to subjects with the CC genotype for the T-786C polymorphism compared to those with TT genotype, at least in terms of the hemorheological properties of erythrocytes.
Keywords: Endothelial nitric oxide synthase; EPR; Genotypes; Nitric oxide; Polymorphisms; Statins